Comparison of actual and predicted anthropometric characteristics of czech elite gymnasts - Kalichová, M.; Hedbavny, P.; Pyrochtová, B.; Prihonská, J. (Science of Gymnastics Journal, 2019)
In context of artistic gymnastics, the influence of intense training on the growth and development of male and female gymnasts is often discussed. The aim of this work is to compare the attained and predicted body height and length of body segments in 11 elite male gymnasts from the Czech Republic who have undergone intense trainings for 12 years or more. The average age of the research sample was 33 ± 11.5 years, body height 174.9 ± 4.1 cm and weight 71.5 ± 5.13 kg. Using standardized anthropometric measurements, we obtained the body height (BH) and length of the trunk, upper and lower limbs, arms, forearms, thighs, and calves. Using the t-test (p .05) ?, a comparison of the actual and predicted body height was made using three different predictive equations. The results were also compared with relative lengths of body segments as reported by Chaffin & Andersson and Brugsch. In most cases, the results indicated lower actual body height than predicted body height, this difference was statistically significant in two of the three predictive equations. The relative predicted length of the upper limbs (0.442BH), arms (0.189BH), lower limbs (0.515BH), thighs (0.257BH) and calves (0.251BH) corresponds with the predicted length of these segments. Actual trunk length (0.544BH) and forearm length (0.166BH) is longer than the predicted length. Based on the analysis of the body segments of the gymnasts we can say that the gymnasts have a longer trunk, medium long upper limbs and shorter lower limbs.